Party down. Season one [videorecording (DVD)] - Scott, Adam, 1973-; Marino, Ken, 1968-; Lynch, Jane, 1960-; Hansen, Ryan; Starr, Martin, 1982-; Caplan, Lizzy, 1982- (Anchor Bay Entertainment, 2010)
A group of struggling dreamers are stuck working for tips while waiting for their big break. As employees of the L.A. catering company 'Party Down, ' these misfits mingle with guests at everything from sweet sixteen parties to the most lavish Hollywood soirees. Follow these engaging wannabes as they wait on guests while waiting on something better to come along.